Infanticide vs. inherited cardiac arrhythmias. Issue 3 (17th November 2020) - Brohus, Malene; Arsov, Todor; Wallace, David A; Jensen, Helene Halkjær; Nyegaard, Mette; Crotti, Lia; Adamski, Marcin; Zhang, Yafei; Field, Matt A; Athanasopoulos, Vicki; Baró, Isabelle; Ribeiro de Oliveira-Mendes, Bárbara B; et al.
Abstract: Aims: In 2003, an Australian woman was convicted by a jury of smothering and killing her four children over a 10-year period. Each child died suddenly and unexpectedly during a sleep period, at ages ranging from 19 days to 18 months. In 2019 we were asked to investigate if a genetic cause could explain the children's deaths as part of an inquiry into the mother's convictions. Methods and results: Whole genomes or exomes of the mother and her four children were sequenced. Functional analysis of a novel CALM2 variant was performed by measuring Ca 2+ -binding affinity, interaction with calcium channels and channel function. We found two children had a novel calmodulin variant ( CALM2 G114R) that was inherited maternally. Three genes ( CALM1-3 ) encode identical calmodulin proteins. A variant in the corresponding residue of CALM3 (G114W) was recently reported in a child who died suddenly at age 4 and a sibling who suffered a cardiac arrest at age 5. We show that CALM2 G114R impairs calmodulin's ability to bind calcium and regulate two pivotal calcium channels (CaV 1.2 and RyR2) involved in cardiac excitation contraction coupling. The deleterious effects of G114R are similar to those produced by G114W and N98S, which are considered arrhythmogenic and cause sudden cardiac death in children. Conclusion: A novel functional calmodulin variant (G114R) predicted to cause idiopathic ventricular fibrillation, catecholaminergic polymorphic ventricular tachycardia, or mild long QT syndrome was present in two children. A fatal arrhythmic event may have been triggered by their intercurrent infections. Thus, calmodulinopathy emerges as a reasonable explanation for a natural cause of their deaths. Graphical Abstract: